The Impact of Dehydration in the Third Trimesters on Pregnancy Outcome-Infant Birth Weight and Length - Mulyani, Erry Yudhya; Hardinsyah, Hardinsyah; Briawan, Dodik; Santoso, Budi Iman (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2018)
This cohort study aimed to analyze the effect of dehydration on pregnancy outcome. A total of 66 pregnant women aged (18-35 years) at second trimester (>12 weeks) of pregnancy was recruited from seven health centers (Puskesmas) Kebon Jeruk, West Jakarta from December 2016 to January 2018. Five biomarkers (urine color, urine osmolality, urine specific gravity, serum osmolality, serum sodium) were utilized to determine hydration status. Based on the result, subjects were then assigned to dehydration group (DG) and normal group (NG), 51.5% was in the DG and 48.5%, in the NG respectively. Independent t-tests and Chi-square were employed to answer research questions. There were differences in weight of the mothers in the second and third trimester between the two groups (p<0.05), but no differences in weight gain during pregnancy (p≥0.05). More than fifty percent of subjects suffered nausea and vomiting during pregnancy in the two groups. Water intake level in DG (72.53±14.41%) were lower than NG (118.68±14.37%). The accounted difference in Infant birth weight, length, chest circumference and head circumference; were 491.84 g, 0.98 cm, 0.98 cm, and 1.11 cm, respectively where infant from the NG had higher measurements than DG. After adjustment for water intake level, the infant birth weight and length in DG (2,798.53±97.85 g; 47.32±0.32 cm) was lower than NG (3,371.77±102.60 g; 49.09±0.33 cm). The accounted difference in infant birth weight and length between the two groups were 596.1 g and 1.8 cm, respectively. Thus in addition to nutrient intake and weight gain during pregnancy, pregnant mothers should also concern for their fluid intake in order to maintain their health condition and feotal growth - development.